Evaluasi Keamanan Sistem Pajak Daerah Online Kabupaten Sumedang Menggunakan Indeks Keamanan Informasi 5.0 - Gita Fitria; Dwi Yuniarto; David Setiadi (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
The digitalization of public services is a priority for local governments to enhance efficiency and transparency. Sumedang Regency has developed the Online Regional Tax Application System (SIAPDOL) to facilitate tax administration. However, SIAPDOL faces significant information security challenges, including data breaches and cyberattacks. This study evaluates SIAPDOL’s security level using the Information Security Index (KAMI) 5.0, which refers to ISO/IEC 27001:2022 standards. The research methodology includes interviews and literature reviews. The results indicate that SIAPDOL has a "Fairly Good" maturity level with a total score of 918, although aspects such as risk management, asset management, and security governance require improvement. Recommendations include developing comprehensive security policies, strengthening risk management procedures, and implementing advanced security technologies. This study contributes academically by providing insights into security evaluations of digital tax systems, while also offering practical recommendations for local governments to enhance the security and reliability of public digital services. Future research can explore AI-driven security solutions, comparative studies with other regions, and the impact of security measures on public trust.